ANALISIS STRUKTUR DAN UNSUR MENULIS TEKS BERITA DALAM HASIL KARYA TULIS SISWA KELAS VII SMP SWASTA METHODIST BERASTAGI TAHUN PEMBELAJARAN 2024/2025 - Br Tarigan, Noveria; Berman Hutahaean; Candra Ronitua Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the structure, elements, errors, and corrections in writing news texts by students of grade VII-2 of Methodist Private Middle School Berastagi in the 2024/2025 Academic Year.The focus of the research includes the application of text structure (title, lead, content, and conclusion), the completeness of the 5W+1H elements (what, who, when, where, why, how), and the use of language in accordance with the General Guidelines for Indonesian Spelling (PUEBI). This research provides theoretical benefits in the development of writing skills studies at the junior high school level, as well as practical benefits for teachers as learning evaluation materials and for students as a means of reflection to improve their writing skills. The method used is descriptive qualitative with data in the form of written works of 30 students analyzed using structural, elemental, and linguistic analysis sheets. Data collection techniques are carried out through documentation, while validity is maintained through diligent observation, peer review, and audit trails. The results of the study indicate that although students have understood the basic structure of news texts, there are still many inaccuracies in arranging the parts of the text logically, as well as incomplete news elements, especially the why and how elements. Linguistic errors such as the use of capital letters, punctuation, and word choice are also still common. Based on these findings, it can be concluded that students' ability to write news texts still needs to be improved, especially in the aspects of completeness of content and accuracy of language. The implications of this study emphasize the importance of more contextual, targeted, and structured practice-oriented writing instruction. The limitations of this study lie in its scope, which only analyzed written output without directly observing the learning process. Therefore, further research is recommended to explore more comprehensive learning strategies to improve students' writing skills.